(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
The general objective of this study was to generate information about the structure of the timber market operating in the state of Acre, between 2018 and 2020. In specific terms, it aimed to identify and analyze the concentration of the local roundwood market in these years. So, the volume of wood harvested during this period was collected in the Exploration AuthorizationsAUTEXs issued by the Instituto do MeioAmbiente do AcreImac. The method adopted used the concepts of the Concentration Ratio and the HerfindahlHirschmanIHH Index. The results obtained showed that: (a) The concentration of roundwood supply in the Acre market was extremely high in 2018 and 2019 and very high in 2020; (b) This supply was extremely concentrated in the 2018-19 period and highly concentrated in 2020; (c) The calculation of the HerfindahlHirschman Index classified the supply of round wood in this market as highly concentrated in 2018 and 2019 and moderately concentrated in 2020 and (d) The IHH also revealed that local firms were highly concentrated in the demand for round wood. Keywords: Forest economy. Market Structure. Forestry-Timber Sector.